Artificial Intelligence as a Mechanism for Transparency and Trust in e-Government: Algorithm for the Detection of Peruvian Marine Species in High Seas During Closed Season - (:unkn) unknown (Springer Nature Switzerland, 2024)
One of the main problems that arise in the process of extracting marine species during the closed seasons is the indiscriminate loading of marine species that are prohibited because they are in spawning season. These problems are often aggravated by the ...
Keywords: Gobierno electrónico; Inteligencia artificial